An Industrial systems study for Spiga Coffee Cartel - Martinez, Deanne A.; Bangalan, Darwin P.; Santos, Rowell Angelo; Serdoncillo, Guy (College of Engineering, 2004)
The study was about Spiga Coffee Cartel, an up and coming entrant in the coffee shop business. This industry is hard to penetrate considering the big names of their competitors. Names such as Starbucks, Seattle's Best, Gloria Jean's, and Figaro, are just some of the names that they have to contend with. In order to be competitive in this business, it is important that they should be able to maximize the utilization of their resources while producing the best for their customers. As with any business, it is important to have an over-all view of the company and to get a clear picture the company should be well documented. The mission and the vision were studied to ensure that the strategies to be developed are in line with the stated vision and mission of the company. Additional analysis were conducted in Spiga Coffee Cartel with the use of SWOT, Seven S Model, and Industry Analysis to determine the position Spiga Coffee Cartel occupies in the specialty coffee shop industry and determine the strategies needed to be developed to improve its position in the market. From the integrated plant audit it was determined that a formal marketing study is needed. Marketing is a very important step because the company controls a very small portion of the market and through marketing; they are banking that their position in terms of market share would be improved. After marketing, it is important to determine whether the current capacity is enough to satisfy the needs of the expected increase in sales. To do this, Queuing analysis was done. Different arrival rates of customers were used in order to determine the limit of the current system. Once this limit was reached, it is time to increase the capacity of the system. After dealing with the capacity requirements of the company, it is now important that the quality of the products being served is acceptable to the customers. In order to ensure this, it is important that a quality policy should be in place to ensure that the materials used and the processes employed are of the highest quality. Lastly, once all these had been done, consideration should be given on the costing of the product. This is to ensure that the products are costed correctly. To do this Activity Based Costing will be used. By using the methods above it is expected that the company can now compete and survive in the industry.